Empowerment, Counseling And Accompaniment For Governance Menarche Toward Students In Ar Rahman Sinadang Kasih South Konawe, Southeast Sulawesi - Yuhanah Yuhanah; Rizka Mutmaina (UNUSA Press, 2022)
Menarche as early menstruation and is the transition from childhood to adolescence (puberty). Manifestations of hormone work during menarche have a significant impact on physical and psychological changes where the development of the body and a sense of mood that has never been felt before such as lazy to study, also women begin to recognize the opposite sex, so this condition makes young women more susceptible to diseases and problems related to reproductive function. It is very important for young women to know personal health from the start before menarche, including body maintenance in the breast and genital area through counseling activities by professions in their fields. The existence of problems encourages the lecturer team to carry out the tridharma of higher education in the form of community service with the hope that when they are teenagers they will be aware, willing and able to behave in a healthy life in order to create a quality future generation of the nation. The implementation of the activity with three stages (Pre-test, counseling and post-test evaluation) took place on 27 May 2022 at the Private Islamic School (SMIS) Ar rahman Sindang Kasih, West Ranomeeto with a team of 2 lecturers. The target objects for female students in grades V and VI were 35 people and the results of the evaluation of the pre-test and post-test questionnaires showed significant changes in students' understanding after counseling, such as 98% not understanding menarche to understanding 95% and 97% being satisfied with the counseling provided. The realization of a quality future generation of women is closely related to the extent to which individuals understand and implement knowledge about personal health, including before menarche. Therefore, the support of various related parties greatly contributes to the progress of the nation.